UNIVERSALITAS ISLAM: MELURUSKAN PANDANGAN BIFURKASI ANTAR ILMU - Noor Hasanah; Mardhiya Agustina (Universitas Islam Negeri Antasari Banjarmasin, 2022)
ABSTRACTThe classification of knowledge is not intended as a bifurcation between general science and religious science. Bifurcation can lead to the misconception that non-religious science is separate from Islam. Whereas in the Islamic intellectual tradition, harmonious unity between science is always maintained. Science is a single entity because the source of all knowledge is the One (al-ahad). The meaning is the concept of science in Islam boils down to the concept of monotheism. Science must be able to bring people closer to the Creator, acknowledge His greatness, encourage people to do good deeds, transform people to be authoritative and respected and be able to offer solutions to crises. So, studying a science does not mean leaving a study of other sciences. This is what is meant by the holistic integration of science. This research is a qualitative research with library method. The focus of this research is to reread the basic principles of science, trace their roots and prove their integration. Keywords: Universality of Islam, Bifurcation, SciencesABSTRAKKlasifikasi ilmu pengetahuan bukan dimaksudkan sebagai bifurkasi antara ilmu umum dan ilmu agama. Bifurkasi dapat memunculkan kesalahan konsepsi bahwa ilmu non agama adalah terpisah dari Islam. Padahal dalam tradisi intelektual Islam, kesatuan yang harmonis antar ilmu senantiasa dijaga. Ilmu adalah kesatuan tunggal karena sumber dari segala ilmu adalah Yang Esa (al-ahad). Maknanya, konsep ilmu dalam Islam bermuara pada konsep tauhid. Ilmu harus dapat mendekatkan manusia kepada Sang Khalik, mengakui keagungan-Nya, mendorong manusia untuk melakukan amal shaleh, mentransformasikan umat menjadi berwibawa dan disegani serta mampu menawarkan solusi terhadap krisis. Sehingga, mempelajari suatu ilmu tidak berarti meninggalkan kajian atas ilmu yang lainnya. Inilah yang dimaksud dengan integrasi ilmu secara holistik. Penelitian ini adalah penelitian kualitatif dengan metode pustaka riset. Fokus penelitian ini adalah untuk membaca ulang prinsip dasar ilmu pengetahuan, melacak akar dan membuktikan keterpaduannya. Kata Kunci: Universalitas Islam, Bifurkasi, Ilmu